LIVE BROADCAST: DEVELOPING PERCEPTUAL SKILLS - Nataliya V. Malkova; Galina V. Kuzmina (Высшее образование в России)
The article is targeted at the difficulties arising in English-language class while working with the TV news content in live broadcast. The article describes some necessary competences and skills, which students should have at various stages for an effective perception of the TV news and other programs transmitted life. Gradual methodology is offered as to acquiring skills by the students regarding comprehension of the above TV programs.